ESTROGEN IN THE TREATMENT OF DEPRESSION: A CASE REPORT - Putu Andrika Kusuma (Universitas Udayana, 2014)
Depression led to the decline quality of life. With more incidence in women due tohormonal cycle caused women more susceptible to depression. Hormone that fluctuatesand holds a key role in brain and nerve cells is estrogen. Estrogen in premenopausalwomen already decreases. Treatment of depression in premenopausal women who gopast the various considerations needs to consider the provision of hormonal therapy. Inthe case of patients treated with psychotherapy and pharmacotherapy in the form of 2 x20 mg Fluoxetine by mouth and hormonal therapy in the form of 1 x 2 mg Estradiol.Feasibility study to evaluate the hormonal therapy contraindications such as breastcancer also needs to be done.